2019
DOI: 10.5152/ejbh.2019.4712
|View full text |Cite
|
Sign up to set email alerts
|

Intramammary Nodal Metastasis from Ovarian Cancer: A Case Report

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Ovarian cancer is one of the most common gynecologic malignancy in the world [1]. However, it generally presents at an advanced stage which is one of the main factors contributing to the high death to incidence rate [2].…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is one of the most common gynecologic malignancy in the world [1]. However, it generally presents at an advanced stage which is one of the main factors contributing to the high death to incidence rate [2].…”
Section: Introductionmentioning
confidence: 99%
“…The rst follows an anterior pathway to the prepericardial nodes then the subclavian lymph trunk ending eventually the axillary lymph nodes, while the other one is posteriorly through inferior diaphragmatic nodes to super cial umbilical lymphatics that end in cisterna chyli that is continuous into the thoracic duct which ends at the junction between the left subclavian and internal jugular veins (9). It should be mentioned that thorough clinical, radiological, and pathological interpretation is crucial to differentiate these patients from primary breast carcinomas with ovarian metastasis (10). In our study, axillary and intramammary nodal metastasis was reported in 7 patients (14.6%), 3 patients presented as a recurrent event through their disease course.…”
Section: Discussionmentioning
confidence: 99%
“…BOM is usually associated with the serous papillary adenocarcinoma subtype, an aggressive and advanced disease, and a poor prognosis [ 9 19 ].As BMs usually develop out of the mammary ductal system, they clinically present as round, rapid growing, painless, and mobile lesions without any cutaneous alteration [ 4 8 ].Radiologically, BMs typically appear as regular lesions without skin infiltration or peri-tumoral desmoplastic reaction [ 4 8 ]. Microcalcifications are rare and usually associated with psammoma bodies in ovarian cancer patients [ 4 9 ].…”
Section: Discussionmentioning
confidence: 99%